A Two-Finger Gripper Actuated by Shape Memory Alloy for Applications in Automation Technology with Minimized Installation Space - Tobias Schmelter; Lukas Bade; Bernd Kuhlenkötter (Actuators)
The increasing demand for innovative grippers and actuators for the automation sector encourages the development of new and innovative functional principles. Intelligent materials are particularly suitable for this purpose based on their high energy density. In this study, a two-finger gripper driven by shape memory alloys (SMA) for use in automation technology is presented. Previous grippers driven by SMA can only be found in the field of micro gripping due to the limited stroke generated by SMA. Based on a methodical product development, a new type of gripper was developed and is presented in this study, which can achieve an opening width comparable to conventional grippers based on transmission mechanisms. Two different variants of the gripper are shown and compared aiming to minimize the installation space and weight of the gripper. In addition to the design presentation, a prototype is built, and the functionality is demonstrated through various test series.